1995
DOI: 10.1073/pnas.92.13.6037
|View full text |Cite
|
Sign up to set email alerts
|

Expression cloning of a cDNA encoding a fish prolactin receptor.

Abstract: By using an expression cloning strategy, we isolated a single positive clone encoding a tilapia prolactin (PRL) receptor. Tilapia PRL188 was used to screen a freshwater tilapia kidney expression library transfected in COS cells. The tilapia PRL receptor is a mature protein of 606 amino acids. The extracellular domain is devoid of the tandem repeat units present in birds and has two pairs of cysteine residues, a Trp-Ser-Xaa-Trp-Ser motif, and two potential N-glycosylation sites. The cytoplasmic domain contains … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
65
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 78 publications
(70 citation statements)
references
References 45 publications
5
65
0
Order By: Relevance
“…The expression of PRLR was analyzed in tilapia by Northern blot and the results obtained demonstrated that the osmoregulatory organs, gills, kidney, and intestine expressed PRLR at higher levels. The ovary, testis, and headkidney (which has hematopoietic function in fish) also expressed PRLR but at much lower levels (Sandra et al, 1995(Sandra et al, , 2000. A similar distribution of PRLR was also observed in the goldfish (Tse et al, 2000).…”
Section: Introductionmentioning
confidence: 52%
See 3 more Smart Citations
“…The expression of PRLR was analyzed in tilapia by Northern blot and the results obtained demonstrated that the osmoregulatory organs, gills, kidney, and intestine expressed PRLR at higher levels. The ovary, testis, and headkidney (which has hematopoietic function in fish) also expressed PRLR but at much lower levels (Sandra et al, 1995(Sandra et al, , 2000. A similar distribution of PRLR was also observed in the goldfish (Tse et al, 2000).…”
Section: Introductionmentioning
confidence: 52%
“…Despite the presence of all the characteristic features of PRLRs, the amino acid sequence of sbPRLR shares a relatively low level of identity with tiPRLR (Sandra et al, 1995) and gfPRLR (Tse et al, 2000). However, sequence identity is higher (46%) in tilapia and goldfish PRLR.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…We also explored the effects of acclimation salinity and extracellular osmolality on the mRNA expression of two Prl receptors (prlr) in the RPD to explore possible feedback mechanisms on Prl expression/ release. Originally cloned by Sandra et al (1995) in Nile tilapia (Oreochromis niloticus), the tilapia Prl receptor (PrlR1) is expressed in an array of tissues, including gill, intestine and kidney (Pierce et al 2007). prlr1 mRNA expression is sensitive to salinity, with enhanced expression occurring in the gill when Mozambique tilapia are transferred from SW to FW (Breves et al 2011) and down-regulated expression after transfer from FW to SW (Breves et al 2010a).…”
Section: Introductionmentioning
confidence: 99%